Immunomodulation and Anti-Inflammatory Effects of Garlic Compounds - Rodrigo Arreola; Saray Quintero-Fabián; Rocío Ivette López-Roa; Enrique Octavio Flores-Gutiérrez; Juan Pablo Reyes-Grajeda; Lucrecia Carrera-Quintanar; Daniel Ortuño-Sahagún (Journal of Immunology Research)
The benefits of garlic to health have been proclaimed for centuries; however, only recently have Allium sativum and its derivatives been proposed as promising candidates for maintaining the homeostasis of the immune system. The complex biochemistry of garlic makes it possible for variations in processing to yield different preparations with differences in final composition and compound proportion. In this review, we assess the most recent experimental results, which indicate that garlic appears to enhance the functioning of the immune system by stimulating certain cell types, such as macrophages, lymphocytes, natural killer (NK) cells, dendritic cells, and eosinophils, by mechanisms including modulation of cytokine secretion, immunoglobulin production, phagocytosis, and macrophage activation. Finally, because immune dysfunction plays an important role in the development and progress of several diseases, we critically examined immunoregulation by garlic extracts and compounds isolated, which can contribute to the treatment and prevention of pathologies such as obesity, metabolic syndrome, cardiovascular disorders, gastric ulcer, and even cancer. We concluded that A. sativum modulates cytokine secretion and that such modulation may provide a mechanism of action for many of their therapeutic effects.